The Impact of Public Investment on Private Investment in the Euro Area - Christian Dreger; Hans-Eggert Reimers (Vierteljahrshefte zur Wirtschaftsforschung, 2015)
This paper explores the long-term relationship between public and private investment in the euro area. A stock-flow approach is proposed to control for the integration properties of the variables. Panel econometric techniques including international spillovers are employed. Private and public capital stocks are cointegrated. However, the residuals from the stock equilibrium are not (trend) stationary, but rather include a random walk component. Nonetheless, they can be exploited to improve the model for private investment flows. In fact, standard models that include private investment flows, GDP, and the real interest rate are only valid if the deviations from the stock equilibrium are considered. The corresponding error correction equation is well behaved, as deviations from the stock relationship are crucial for explaining the changes in private investment. Thus, the lack of public investment may have been restricting private investment and GDP growth in the euro area.
Keywords: C23; E22; E62; 330; Public and private investment; capital stocks; fiscal austerity